A Semi-Analytical Mathematical Model for Off-Center Fractured Vertical Wells With Asymmetrical Fractures in Columnar Coalbed Methane - Ji, Anzhao; Chen, Zhanjun; Wang, Yufeng; Zhang, Guangsheng; Mao, Zhenglin; Chen, Fenjun (Frontiers in Energy Research, 2022)
As an important unconventional oil and gas resource, coalbed methane (CBM) is usually exploited by hydraulic fracturing technology. Since most of the wells are not at the center of the reservoir, it is of great significance to analysis the wellbore pressure characteristic of off-center fractured vertical wells. The adsorption–desorption, fracture asymmetry are considered. The pressure wellbore solution of off-center fractured well can be obtained by Laplace transformation, discretization method and Gauss elimination. Then, the Stehfest numerical inversion is utilized to obtain the pressure solution and rate distribution in real-time domain. This semi-analytical model is verified, The results show that the wellbore pressure include six flow regimes. The effects on pressure behavior of fracture angle, dimensionless conductivity and distance from wellbore to coal gas reservoirs center are discussed.